Medida da visão em candelas: descrição de uma técnica psicofísica para quantificar intensidade luminosa - Kronbauer, Airton Leite [UNIFESP] (2011)
Purpose: To develop a method and a device for vision measurement in candela (cd). Vision measurement studies are important to all visual sciences.Methods: It is a theoretical and experimental study. The details of psychophysical method and device calibration were described. Preliminary tests were performed on volunteers.Results: It is a simple psychophysical test and results are expressed in International System of Units. With this technical description it will be possible to reproduce the experiment in others research centers.Conclusion: The results measured in luminous intensity (cd) are an option for visual studies. These results allow to extrapolate measurements for mathematical models and to simulate data for individual aberrometry effects.